Effects of high-intensity interval training protocols on blood lactate levels and cognition in healthy adults: systematic review and meta-regression - Jacob, N.; So, I.; Sharma, B.; Marzolini, S.; Tartaglia, M. C.; Oh, P.; Green, R. (Sports Medicine, 2023)
Background: Some health benefits from high-intensity interval training (HIIT) are facilitated by peripheral blood lactate levels. However, the lactate response from HIIT is variable and dependent on protocol parameters. Objectives: We aimed to determine the HIIT protocol parameters that elicited peak lactate levels, and how these levels are associated with post-HIIT cognitive performance. Study Design: We conducted a systematic review with meta-regression. Methods: MEDLINE, Embase, CENTRAL, SPORTDiscus, and CINAHL + were searched from database inception to 8 April, 2022. Peer-reviewed primary research in healthy adults that determined lactate (mmol/L) and cognitive performance after one HIIT session was included. Mixed-effects meta-regressions determined the protocol parameters that elicited peak lactate levels, and linear regressions modelled the relationship between lactate levels and cognitive performance. Results: Study entries (n = 226) involving 2560 participants (mean age 24.1 ± 4.7 years) were included in the meta-regression. A low total work-interval volume (~ 5 min), recovery intervals that are about five times longer than work intervals, and a medium session volume (~ 15 min), elicited peak lactate levels, even when controlling for intensity, fitness (peak oxygen consumption) and blood measurement methods. Lactate levels immediately post-HIIT explained 14-17% of variance in Stroop interference condition at 30 min post-HIIT. Conclusions: A HIIT protocol that uses the above parameters (e.g., 8 × 30-s maximal intensity with 90-s recovery) can elicit peak lactate, a molecule that is known to benefit the central nervous system and be involved in exercise training adaptations. This review reports the state of the science in regard to the lactate response following HIIT, which is relevant to those in the sports medicine field designing HIIT training programs.